Variation in reproductive effort, genetic diversity and mating systems across Posidonia australis seagrass meadows in Western Australia. Issue 4 (6th August 2020) - Sinclair, Elizabeth A; Edgeloe, Jane M; Anthony, Janet M; Statton, John; Breed, Martin F; Kendrick, Gary A
Abstract: Populations at the edges of their geographical range tend to have lower genetic diversity, smaller effective population sizes and limited connectivity relative to centre of range populations. Range edge populations are also likely to be better adapted to more extreme conditions for future survival and resilience in warming environments. However, they may also be most at risk of extinction from changing climate. We compare reproductive and genetic data of the temperate seagrass, Posidonia australis on the west coast of Australia. Measures of reproductive effort (flowering and fruit production and seed to ovule ratios) and estimates of genetic diversity and mating patterns (nuclear microsatellite DNA loci) were used to assess sexual reproduction in northern range edge (low latitude, elevated salinities, Shark Bay World Heritage Site) and centre of range (mid-latitude, oceanic salinity, Perth metropolitan waters) meadows in Western Australia. Flower and fruit production were highly variable among meadows and there was no significant relationship between seed to ovule ratio and clonal diversity. However, Shark Bay meadows were two orders of magnitude less fecund than those in Perth metropolitan waters. Shark Bay meadows were characterized by significantly lower levels of genetic diversity and a mixed mating system relative to meadows in Perth metropolitan waters, which had high genetic diversity and a completely outcrossed mating system. The combination of reproductive and genetic data showed overall lower sexual productivity in Shark Bay meadows relative to Perth metropolitan waters. The mixed mating system is likely driven by a combination of local environmental conditions and pollen limitation. These results indicate that seagrass restoration in Shark Bay may benefit from sourcing plant material from multiple reproductive meadows to increase outcrossed pollen availability and seed production for natural recruitment. Abstract : Plant species including seagrasses reproduce using sexual (seeds) and asexual (vegetative) means which can vary across a species range. We compare sexual reproduction, genetic diversity and the mating system in Posidonia australis seagrass meadows from Western Australia. Flower and fruit production were two orders of magnitude lower in Shark Bay meadows which also had lower genetic diversity and a mixed mating system when compared with meadows in Perth metropolitan waters. These results indicate that seagrass restoration in Shark Bay may benefit from sourcing plant material from multiple reproductive meadows to increase outcrossed pollination and seed production for natural recruitment.